2021
DOI: 10.3389/fpsyg.2021.619345
|View full text |Cite
|
Sign up to set email alerts
|

Double-Edged Sword Effect of High-Performance Work System on Employee Well-Being—Moderating Effect of Union Practice

Abstract: Improving the well-being of the employees is the inevitable choice to improve corporate performance and competitive advantage and the social responsibility that enterprises must undertake. Based on the job demands-resources model, this study introduces perceived organizational support and work stress as the mediator and trade union practice as the moderator to explore the double-edged sword effect of a high-performance work system (HPWS) on the well-being of the employee. Taking 243 employees from Jiangsu, Zhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
10
0
3
Order By: Relevance
“…The dominating assumption is that HPWS increases job demands ( Han et al, 2020 ). More specifically, we need an explanation for why the main effects of HPWS on job demands/stress is sometimes negative (e.g., Kloutsiniotis and Mihail, 2020 ; the present study) and sometimes positive ( Ramsay et al, 2000 ; Kroon et al, 2009 ; Jensen et al, 2013 ; Ogbonnaya and Messersmith, 2019 ; Qi et al, 2021 ; Zhu et al, 2022 ). One explanation may be omitted leadership variables, either in terms of their main effects (as in the present study) or as moderating substitutes (e.g., Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The dominating assumption is that HPWS increases job demands ( Han et al, 2020 ). More specifically, we need an explanation for why the main effects of HPWS on job demands/stress is sometimes negative (e.g., Kloutsiniotis and Mihail, 2020 ; the present study) and sometimes positive ( Ramsay et al, 2000 ; Kroon et al, 2009 ; Jensen et al, 2013 ; Ogbonnaya and Messersmith, 2019 ; Qi et al, 2021 ; Zhu et al, 2022 ). One explanation may be omitted leadership variables, either in terms of their main effects (as in the present study) or as moderating substitutes (e.g., Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 71%
“…The mechanism of the latter remained unidentified in the present study. Together this emerging evidence calls into question the robustness and generalizability of theorizing ( Han et al, 2020 ) and empirical research that has found HPWS directly and positively related to work intensification ( Ramsay et al, 2000 ; Kroon et al, 2009 ; Jensen et al, 2013 ; Ogbonnaya and Messersmith, 2019 ; Qi et al, 2021 ; Zhu et al, 2022 ; see also Ehrnrooth and Bjorkman, 2012 ). Specifically, the change in the relationship between HPWS and job demands when accounting for TL in the present study was significant enough to shed some more doubt on the received view of the nature of this relationship (more on this in the next section).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor included five items, which reflected the concern of medical personnel about their specific work content and job responsibilities. Several studies [ 62 64 ] have documented that a strong correlation between job characteristics (such as job content and stress) and job-related happiness, and come up with strategies for improving employees’ job-related happiness from the perspective of job responsibility. Job-related happiness is closely related to career choice, so job responsibility is an important influencing factor for employees’ career choices.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the “maintenance of order” function of the enterprise trade unions, which is stipulated in the Trade Union Law, also requires it to assume the responsibility of maintaining the stability of enterprise production and mobilizing productivity in employees (Wang and Zheng, 2012 ). However, at present, trade unions still regard serving employees and protecting their rights and interests as their primary responsibility (Qi et al, 2021 ). This demonstrates that through the process of interaction between the trade unions and human resource management, each other's content and method of engagement have changed, but their purpose and service objective have not changed.…”
Section: The Characteristics Of the Coupling Relationshipmentioning
confidence: 99%